THINKING FOR THEMSELVES: EXAMINING THE REACTIONARY RIGHT’S "BOOTSTRAPS EPISTEMOLOGY" - Ma, Cindy (AoIR Selected Papers of Internet Research, 2023)
This paper offers a new way of conceptualizing conservatives’ approach to truth and knowledge, based on over two years of online fieldwork (2019-2021) into reactionary YouTube channels and their audiences. I use qualitative content analysis to examine over 100 hours of YouTube videos, 1050 YouTube comments, and online interviews with 15 current and former fans of these channels. Drawing on these data sources, I argue that the reactionary right’s emphasis on “rugged individualism” forms the basis not just of their political project but also of their imagined epistemology. I find that reactionary YouTubers and their viewers describe arriving at their political beliefs as a highly idiosyncratic process of personal research and rational deliberation. I call this narrative of political formation "bootstraps epistemology." Just as the bootstraps narrative in politics argues that individuals have the duty to reject government “handouts” and improve their circumstances through hard work and thrift, bootstraps epistemology encourages people to reject dogma and instead pursue knowledge through solitary study and intellectual combat with opponents. I propose that the bootstraps narrative of personal responsibility and bootstraps epistemology are mutually-enforcing discourses that advance individualistic solutions to social problems. I find that the latter has gained currency in recent years, with the widespread loss of trust in mainstream media and the proliferation of “alternative” sources of onli news and information.